A CRISPR-Cas12b–Based Platform for Ultrasensitive, Rapid, and Highly Specific Detection of Hepatitis B Virus Genotypes B and C in Clinical Application - Chen, Xu; Tan, Yan; Wang, Shuoshi; Wu, Xueli; Liu, Rui; Yang, Xinggui; Wang, Yi; Tai, Jun; Li, Shijun (Frontiers in Bioengineering and Biotechnology, 2021)
Hepatitis B virus (HBV) is one of the most dangerous and prevalent agents that causes acute and chronic liver diseases in humans. Genotyping plays an important role in determining clinical outcomes and response to antiviral treatment in HBV–infected patients. Here, we first devised a CRISPR–based testing platform, termed “CRISPR-HBV,” for ultrasensitive, highly specific, and rapid detection of two major HBV genotypes (HBV-B and HBV-C) in clinical application. The CRISPR-HBV employed multiple cross displacement amplification (MCDA) for rapid preamplification and then Cas12b–based detection for decoding the targets. Finally, the detection result was read out with real-time fluorescence and a lateral flow biosensor. The sensitivity of CRISPR-HBV was 10 copies per test. The specificity was one hundred percent, and no cross reactions were observed in other HBV genotypes and pathogens. The whole detection process, including DNA template extraction (15 min), preamplification reaction of MCDA (30 min at 65°C), CRISPR-Cas12b–based detection (5 min at 37°C), and results readout (∼2 min), could be completed within 1 h. The feasibility of the CRISPR-HBV assay for genotyping HBV-B and -C as successfully validated with clinical samples. Hence, the CRISPR-HBV assay has remarkable potential to develop a point-of-care testing for identifying and distinguishing HBV genotypes B and C in clinical settings, especially in resource-scarcity countries.